2020
DOI: 10.1007/s00403-020-02145-3
|View full text |Cite
|
Sign up to set email alerts
|

Teledermatology: current indications and considerations for future use

Abstract: Telemedicine is one of the most consequential technologies in modern healthcare. In certain situations, it allows for the delivery of care with high quality and minimal difficulty. This is particularly true in dermatology, in which many dermatological conditions can be treated remotely. The burden on dermatology patients has been greatly reduced for certain pathologies due to telemedicine. Health care providers also achieve improved job satisfaction following the convenience of meeting their patients. This pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 28 publications
0
33
0
Order By: Relevance
“…As previously mentioned, patients living in rural areas have limited access to dermatologists [ 6 ], often being forced to travel great distances for in-person dermatology appointments. By providing at-home care, TD cuts travel costs for patients and eliminates time spent driving to a doctor’s office [ 10 ]. In addition to reduced travel costs, a 2019 study in Philadelphia revealed that TD reduces medical costs for patients because timely access to care provided by TD reduces urgent care and emergency department visits.…”
Section: Discussionmentioning
confidence: 99%
“…As previously mentioned, patients living in rural areas have limited access to dermatologists [ 6 ], often being forced to travel great distances for in-person dermatology appointments. By providing at-home care, TD cuts travel costs for patients and eliminates time spent driving to a doctor’s office [ 10 ]. In addition to reduced travel costs, a 2019 study in Philadelphia revealed that TD reduces medical costs for patients because timely access to care provided by TD reduces urgent care and emergency department visits.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Anderesen et al, through a retrospective review of the teledermatology database in the Faroe Islands, a group of 18 islands in the North Atlantic, concluded that teledermatology is indispensable in specific contexts, such as rural areas, while in non-rural ones, should be destined to evaluate which disease can benefit from either in-person or online visits to give selectivity on resources destined for telemedicine [ 12 ]. Moreover, since the worldwide spread of the SARS-CoV-2 infection at the end of 2019, telemedicine has gained an increasingly important role in daily clinical practice, especially regarding patients affected by chronic diseases, such as psoriasis [ 16 , 17 ]. Villani and colleagues implemented an already existing teleconsultation service that was originally reserved for emergencies, and that turned routine during the COVID-19 pandemic, given the need to avoid social contacts [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Such measures appeared to be very important, particularly for those patients under immunosuppressive drugs that were at high risk of contracting the infection [ 13 ]. In general, Beer, Chambers, Pearlman, and Frühauf accordingly reported in their studies that online interactions were well accepted by patients and highly preferred to in-person visits [ 16 , 17 , 18 , 19 ]. Moreso, Yi et al noticed a slight decrease in access to telehealth services for elderly and non-English speaker patients, suggesting potential unequal access to care for these vulnerable patients [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, expanding the training set could substantially increase the performance of the CNN CORAL for automated PASI scoring. With the increasing interest in tele-dermatology and at-home hospital care, 28 image-based automated PASI scoring by CNNs may not only provide objective PASI scoring in clinical practice and research, but may facilitate reliable psoriasis severity assessments for remote consultations in the future by incorporating the algorithm into a mobile application that could be used at home. In conclusion, CNNs have the potential to automatically perform image-based PASI scoring at an anatomical region level.…”
Section: Discussionmentioning
confidence: 99%